Response of Plant Leaf Traits to Environmental Factors in Climax Communities at Varying Latitudes in Karst Regions - Gang Xie; Yang Wang; Zhifeng Chen; Yangyang Ji; Yao Lu; Yi Liang; Ruiyu Zhou; Juan Tao (Plants)
Exploring the changes in plant functional traits and their relationship with the environment in karst climax communities across different latitudes can enhance our understanding of how these communities respond to environmental gradients. In this study, we focus on climax karst climax plant communities in Guizhou Province, China. We selected three sample sites located at varying latitudes and analyzed the variations in functional traits of the plant communities at these latitudes. Additionally, we examined the relationship between functional traits and environmental factors, integrating species characteristics and community structure into our analysis. The results indicated that (1) there were significant differences in both the community leaf aspect ratio and the community-specific leaf area. (2) Soil organic carbon content exhibited significant variations across different latitudes, while soil nitrogen content was notably higher in mid-latitude and low-latitude regions compared to high-latitude areas. The distribution of soil factors was more concentrated in high and mid-latitude regions, whereas low-latitude areas displayed more pronounced variability. (3) The primary environmental factors influencing the climax community in the karst study area included soil water content (SPMC), soil bulk density (BD), soil organic carbon content (SOC), soil nitrogen content (SNC), and soil phosphorus content (SPC). Our findings suggest that karst plant communities exhibit specific combinations of functional traits at distinct latitudes. With increasing latitude, the community demonstrated a gradual shift in ecological strategy from conservative to more opportunistic. Most environmental factors imposed limiting effects on plant functional traits, with plants primarily constrained by BD during growth. Among the responses of plant functional traits to environmental factors, community-weighted leaf area and community-weighted chlorophyll content were the most sensitive to soil conditions.